E-Procurement For Small and Medium Enterprises In Malaysia - Polit, Zakaria (Universiti Teknologi Petronas, 2004)
This report is the documentation of progress report for Final Year Project titled " E~ Procurementfor Small andMedium Enterprises (SMEs) inMalaysia". This research was initiated due to the interest on the E-Procurement issues for the small and medium enterprises (SMEs) in Malaysia. It will look at the reasons behind the reluctance of the companies in implementing the E-Procurement System, and also this research will hopefully come up with a system that meets the requirements ofthe respective companies. The scope of study encompasses the small and medium companies in Malaysia. A definition of such companies can befound here, which the research will follow so that the research would not go out of scope. Malaysia is chosen as it is where theresearch is being conducted. The methodology for this study was comprised of five stages, namely; planning, data collection, data compilation and analysis, prototype design and testing. To realize this research, a few tools would be used to meet the objectives.